National Consensus on the Use of Sedation Drugs in the Gastrointestinal Endoscopic Procedures - Daldiyono Daldiyono; Abdul Aziz Rani; Marcellus Simadibrata; Ari Fahrial Syam; Achmad Fauzi; Dadang Makmun; Murdani Abdullah; Indra Marki; Kaka Renaldi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2017)
Gastrointestinal endoscopy is rapidly developing and several gastrointestinal endoscopy equipment are available for both diagnostic and therapeutic purposes. Proper sedation is critical in performing endoscopic procedures, both for patients and physicians. This consensus is used as a guideline and not as a legal standard in performing endoscopic services. This consensus explained the definition, indication, contraindication, and complication prevention during sedation. Factors affecting the need of sedation is patient factors, procedure factors, and sedation level. Diagnostic or therapeutic upper gastrointestinal tract endoscopy which not complicated can be performed with minimal sedation or moderate sedation, while deep sedation can be considered for longer and more complex procedures. Furthermore, assessment and selection of sedation was explained, followed by the guide to choose pharmacological sedation and analgesics. Currently, diazepam, midazolam, propofol, fentanyl, and pethidine is the most likely used sedation during gastrointestinal endoscopy, with midazolam as the preferred medication of choice. This consensus also explained the antidote of each drug and the recovery after procedure. This consensus aimed to improve gastrointestinal endoscopic procedure services in Indonesia.